FAMILY CHARACTERISTICS OF CHILDREN UNDER FIVE YEARS OLD AND MOTHERS WITH ANEMIA IN INDONESIA - Nurhidayati, Nuzuliyati; Djaiman, Sri Poedji Hastoety (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
The prevalence of anemia in Indonesia shows an increase. Anemia in children and mothers has serious health effects. This analysis aims to better understand the characteristics of toddlers and their mothers with concurrent anemia in the same family. The analysis uses Riskesdas data from 2018 with a cross-sectional design. Sampling is done using a probability proportional to the size. The samples analyzed were families with toddlers and mothers with toddlers with Hb measurement data and other supporting data. The analysis was performed descriptively and another proportionality test was performed using the Chi-Square test (p<0.05). The results of the analysis showed that 38.9% of toddlers were anemic, 21.3% of mothers with children under 5 years of age were anemic, while children and mothers in the same family had anemia 9.7. %. In families with children and mothers, anemia often occurs in families with low economic status, the education level of the household head is not high, the number of family members is more than 4 people, the number of children under 5 years old in the family is less. households with ≤2 children, living in rural areas and living outside Java and Bali area (10.7%; 10.0%; 12.2%; 9.7%; 10.0–12.0%). The high prevalence of anemia in households suggests that anemia management still needs to be improved. All family members can play an independent role in monitoring and early detection of anemia symptoms in toddlers and their mothers.